2019
DOI: 10.1016/j.eats.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Assisted Reduction in a Chronic Locked Posterior Shoulder Dislocation

Abstract: Neglected posterior shoulder dislocation is a difficult condition in terms of decision making and surgical technique. Not only the bony deformity but also the soft tissue and patient's underlying disease are of concern. Whether the poor results are associated with a time delay or the treatment method is not clear yet. To date, there is neither a consensus nor treatment guidelines. We describe an arthroscopically assisted reduction and open McLaughlin procedure. The advantage of this procedure is preservation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…However, we believe that their case was not a typical chronically locked case because in a typical case, the locked humeral head prevents glenohumeral access through the routine posterior portal and the only window by which to reach the glenohumeral joint is through the rotator interval. Prasathaporn et al 5 reported an arthroscopy-assisted reduction case. In their case, the arthroscopic technique was used just for debridement outside the rotator interval, whereas open procedures were used to access the glenohumeral joint and perform reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we believe that their case was not a typical chronically locked case because in a typical case, the locked humeral head prevents glenohumeral access through the routine posterior portal and the only window by which to reach the glenohumeral joint is through the rotator interval. Prasathaporn et al 5 reported an arthroscopy-assisted reduction case. In their case, the arthroscopic technique was used just for debridement outside the rotator interval, whereas open procedures were used to access the glenohumeral joint and perform reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Prasathaporn et al. 5 reported an arthroscopy-assisted reduction case. In their case, the arthroscopic technique was used just for debridement outside the rotator interval, whereas open procedures were used to access the glenohumeral joint and perform reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El manejo inicial es funcional en la mayoría de los casos con un 80% de éxito en casos de hiperlaxitud o en ausencia de anormalidad del hueso. (11). Aproximadamente el 50% de estas luxaciones están asociadas con lesiones de Hill-Sachs inversas, que es una fractura por impactación de la cara anteromedial de la cabeza humeral, puede pasarse por alto en hasta el 60% de los casos (12).…”
Section: Caracteristicas De La Luxacion Posterior De La Articulacion Glenohumeralunclassified
“…This can decrease the presence of fibrous tissue and lower the risk of iatrogenic fractures during reduction maneuvers. 7 , 8 , 9 , 10 …”
mentioning
confidence: 99%